Sundanese Translation of English Terms of Address - Sukaesih, Ina; M., R. Nababan; Santosa, Riyadi; Djatmika (International Journal of Psychosocial Rehabilitation, 2020)
The article addresses English and Sundanese terms of address. It studies the varieties of translated English terms of address in Sundanese novel Pependeman Nabi Sulaeman. Terms of address are considered necessary in cross-cultural communication; therefore, one needs to have a great understanding of their usage. This article will discuss the classification of terms of address, the translation techniques used, and the translation quality of their Sundanese translation. The article will also look at the sociolinguistic angle, which involves speakers’ relations. Interlocutors’ relationships, which are influenced by power and intimacy, are realized in Sundanese polite language (lemes) and rude language (loma). As Sundanese applies speech levels as the representation of its culture, it will also argue about the appropriateness of the usage of the words for the first speaker, the second speaker, and the person discussed. The data are collected using content analysis and focus discussion groups, and we analyzed them under the Spreadly procedure. From the source text of King Solomon’s Mines, there are two classifications of terms of address, i.e., nominal and pronominal. The dominant deletion translation technique used impacts the translation quality negatively. Those different translation versions found are translated appropriately seen from the angles of speakers’ power and intimacy, and are relatively in acceptable word usage.